Sebelas Tahun Perkembangan Jagung Bt dan Statusnya secara Global - M. Herman (Balai Besar Penelitian dan Pengembangan Bioteknologi dan Sumber Daya Genetik Pertanian, 2007)
Major insect pests of corn are the Asiancorn borer, the European corn borer, and the corn rootworm. The value of crop losses due to the insect pests inAmerica is 2.6 billion, Asia 1.6 billion, Africa 0.8 billion,and Europe 0.6 billion. Prior to the use of Bt corn, farmersused a lot of insecticides to control the insect pests.Following introduction of the Bt corn in 1996, this crop hasbeen grown over 21 million hectares by millions of farmersfrom 13 countries in North America, Latin America, Asia,Africa and Europe. Globally, the farmers had been benefitedby grownt the Bt corn. The benefits varies, dependent oncountries and level of the corn borer infestations. In 2001,the US farmers gained 125 million benefit from growing thecrop. In 2002, farmers in Spain gained 11-15 million benefitfrom the Bt corn alone. During the period of 2003-2005, cornfarmers in the Philippines gained 8 million from the Bt corn.Bt corn has not been grown commercially in Indonesia,although Bt corn MON810 has been declared as save torelease in the environment by the Indonesian BiosafetyCommittee. In 2001-2002, farmers in South Sulawesi withhad grown Bt cotton, this was the first time Bt crop in thecountry since the placement and implementation of thebiosafety regulation by the Indonesian Government in 1998.